Fetal phenotype associated with the 22q11 deletion. Issue 11 (8th August 2014) - Noël, Anne‐Claire; Pelluard, Fanny; Delezoide, Anne‐Lise; Devisme, Louise; Loeuillet, Laurence; Leroy, Brigitte; Martin, Alain; Bouvier, Raymonde; Laquerriere, Annie; Jeanne‐Pasquier, Corinne; Bessieres‐Grattagliano, Betty; Mechler, Charlotte; et al.
ABSTRACT The 22q11 deletion syndrome is one of the most common human microdeletion syndromes, with a wide spectrum of abnormalities. The fetal phenotype associated with the 22q11 deletion is poorly described in the literature. A national retrospective study was performed from 74 feto‐pathological examinations. The objectives were to evaluate the circumstances of the 22q11 deletion diagnosis and to describe fetal anomalies. Post mortem examinations were performed after 66 terminations of pregnancy and eight fetal deaths. The series included nine fetuses from the first trimester, 55 from the second trimester, and ten from the third trimester. A 22q11 FISH analysis was recommended for 57 fetuses after multidisciplinary prenatal diagnostic counseling and for 17 fetuses by a fetal pathologist. Conotruncal heart defects were the most common anomalies (65 fetuses), followed by thymus defects (62 fetuses), and malformations of the urinary tract (25 fetuses). This study identified several unusual and severe features rarely described in the literature. Neurological abnormalities were described in ten fetuses, with seven neural tube defects and five arhinencephalies. This series also included lethal malformations: two hypoplastic left heart syndromes, two bilateral renal agenesis, and one tracheal agenesis. Genetic analysis for a 22q11 deletion is usually indicated when a congenital conotruncal heart and/or thymus defect is detected, but might also be useful in case of other lethal or severe malformations that initially led to the termination of pregnancy. © 2014 Wiley Periodicals, Inc.